Perancangan Dan Implementasi Sistem Kendali Kursi Roda Berbasis Mikrokontroler - Mardianto, Eko; Tarkan, Rianda; Syahrizan, Syahrizan; Satriyo, Satriyo (entries, 2024)
This research aims to develop a wheelchair control system based on a microcontroller using Arduino Uno, a joystick, and Bluetooth HC-05 for wireless connectivity. The goal is to enhance the affordability and comfort of wheelchair users through this control system. Arduino Uno serves as the main control unit, receiving input from the joystick. Wireless connection utilizes Bluetooth HC-05 technology, providing flexibility for remote operation. The system design involves selecting appropriate sensors and actuators to ensure responsiveness and everyday safety. This innovation eliminates the need for wheelchair users to manually operate it with significant effort. The control system provides an opportunity for those with physical limitations to be independent and enhance mobility in daily activities. With this solution, wheelchair users can experience greater independence and participate more actively in various activities.